Development of the CORE-Kids core set of outcome domains for studies of childhood limb fractures. (1st December 2021) - Marson, Ben A.; Manning, Joseph C.; James, Marilyn; Craxford, Simon; Deshmukh, Sandeep R.; Perry, Daniel C.; Ollivere, Benjamin J.; ,
Abstract : Aims: The aim of this study is to develop a core set of outcome domains that should be considered and reported in all future trials of childhood limb fractures. Methods: A four-phase study was conducted to agree a set of core outcome domains. Identification of candidate outcome domains were identified through systematic review of trials, and outcome domains relevant to families were identified through semi-structured interviews with 20 families (parent-child pairing or group). Outcome domains were prioritized using an international three-round Delphi survey with 205 panellists and then condensed into a core outcome set through a consensus workshop with 30 stakeholders. Results: The systematic review and interviews identified 85 outcome domains as relevant to professionals or families. The Delphi survey prioritized 30 upper and 29 lower limb outcome domains at first round, an additional 17 upper and 18 lower limb outcomes at second round, and four additional outcomes for upper and lower limb at the third round as important domains. At the consensus workshop, the core outcome domains were agreed as: 1) pain and discomfort; 2) return to physical and recreational activities; 3) emotional and psychosocial wellbeing; 4) complications from the injury and treatment; 5) rturn to baseline activities daily living; 6) participation in learning; 7) appearance and deformity; and 8) time to union. In addition, 9a) recovery of mobility and 9b) recovery of manual dexterity was recommended as a core outcome for lower and upper limb fractures, respectively. Conclusion: This set of core outcome domains is recommended as a minimum set of outcomes to be reported in all trials. It is not an exhaustive set and further work is required to identify what outcome tools should be used to measure each of these outcomes. Adoption of this outcome set will improve the consistency of research for these children that can be combined for more meaningful meta-analyses and policy development. Cite this article: Bone Joint J  2021;103-B(12):1821–1830.